2005
DOI: 10.1111/j.1745-7270.2005.00051.x
|View full text |Cite
|
Sign up to set email alerts
|

Carboxyfluorescein Diacetate Succinimidyl Ester Fluorescent Dye for Cell Labeling

Abstract: Our objective was to study the properties of the carboxyfluorescein diacetate succinimidyl ester (CFDA-SE) and the methodology of cell labeling using CFDA-SE fluorescent dye. First, we analyzed the kinetics of CFDA-SE fluorescent dye intensity over time. Second, we determined the optimal concentration of CFDA-SE fluorescent dye for cell labeling. Third, we tested the toxicity of CFDA-SE fluorescent dye on labeled cells. Finally, we determined the optimal staining time of CFDA-SE fluorescent dye for cell labeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 15 publications
1
48
0
Order By: Relevance
“…16 Effects of supravital dyes, such as CFSE, would ideally be inert with respect to other cellular functions, such as secretion of PRG4 and matrix accumulation. The inertness of CFSE labeling on PRG4 secretion by superficial chondrocytes is consistent with its lack of adverse effects on cell viability 25,27 and growth. 38 In the present study, PRG4 secretion levels were generally comparable to those found previously for S and M zone chondrocytes in monolayer culture, 16,42 with S cells secreting significantly more PRG4 than M cells.…”
Section: Figmentioning
confidence: 54%
See 1 more Smart Citation
“…16 Effects of supravital dyes, such as CFSE, would ideally be inert with respect to other cellular functions, such as secretion of PRG4 and matrix accumulation. The inertness of CFSE labeling on PRG4 secretion by superficial chondrocytes is consistent with its lack of adverse effects on cell viability 25,27 and growth. 38 In the present study, PRG4 secretion levels were generally comparable to those found previously for S and M zone chondrocytes in monolayer culture, 16,42 with S cells secreting significantly more PRG4 than M cells.…”
Section: Figmentioning
confidence: 54%
“…22,23 CFSE has been used to track various cell types in vitro and in vivo [24][25][26] and, similar to lipophilic dyes, can be applied to track generations of cells since the associated fluorescence signal decreases by half with each cell division cycle. CFSE does not appear to have adverse effects on cell function and cell viability, 27 indicating that it could be useful for tracking chondrocytes in cell-laden tissues implanted in vivo and could be applied in conjunction with other labeling probes, such as PKH26, to track more than one type of cell population in parallel.…”
mentioning
confidence: 99%
“…The same holds true for rhodamine 6G, the widely applied dye for in vivo labelling of leukocytes for IVM studies [7,8]. In contrast, carboxyfluorescein diacetate succinimidyl ester (CFDA-SE) has been rarely applied for IVM investigations [9][10][11] even though it is discussed as an ideal dye for flow cytometry-based proliferation studies [5,6,12].…”
Section: Biophotonicsmentioning
confidence: 99%
“…Today, in vivo fluorescent labelling has proved to be the preferred method for labelling cells for IVM, thus avoiding some of the disadvantages of ex vivo labelling with radioactive isotopes [5]. In the context of IVM investigations, several dyes for leukocyte labelling have been applied for the analysis of leukocyte recruitment.…”
Section: Biophotonicsmentioning
confidence: 99%
“…General protein labelling CFSE acts by forming random covalent bonds with amino groups on cellular proteins, which results in a highly fluorescent membrane impermeable marker 29 . The reduced amount of CFSE due to daughter cells shared the dye, which homogeneously adhered to all compounds of the cells.…”
mentioning
confidence: 99%